Paulus se retoriese strategie in Galasiërs 1:1-10: Paul’s rhetorical strategy in Galatians 1:1-10 - Tolmie, DF (Acta Theologica, 2000)
The aim of this article is to demonstrate an approach to the rhetorical analysis of Paul’s Letter to the Galatians that differs from the typical approach followed by researchers, namely the forcing of ancient rhetorical categories on the letter. Instead it is proposed that Paul’s rhetorical strategy should be analysed in terms of a "grounded theoretical approach". This is demonstrated by a systematic analysis of the Paul’s basic rhetorical strategy, as well as of all the supportive pursuasive techniques, in these two pericopes.